Spectroscopic, quantum computational and molecular docking studies on 1-phenylcyclopentane carboxylic acid. (October 2019) - Raajaraman, BR; Sheela, N.R.; Muthu, S.
Graphical abstract: Highlights: Experimental and computed spectra of 1PCPCA agrees with each other. The reactive areas of 1PCPCA are calculated by MEP and Fukui function. The inter and intra molecular interactions are calculated by NBO. Ligand and proteins docking studies suggest 1PCPCA as a potential anticancer drug. Abstract: The vibrational wavenumbers of optimized molecular structure of 1-phenylcyclopentane carboxylic acid (1PCPCA) molecule have been calculated by quantum chemical theory and compared with experimental results. The density functional theory (DFT) approach is followed using the method B3LYP and 6-311++G(d, p) basis set. Using potential energy distribution, all the assignments of the basic vibrational modes were calculated. Natural bond orbital (NBO) and atoms in molecules (AIM) topological studies applied to get the intermolecular interactions of the compound. 1 H and 13 C chemical shift of NMR was estimated on the molecule and also compared with the experimental spectra. In order to find the band gap, the time-dependent (TD-DFT) method is used to get the higher order energy levels properties and also compared with experimental data of UV–vis spectrum. From the analysis of various spectroscopic studies, there is a good relationship between the experimental and theoretical values obtained. Quantum characters, bio-active nature and reactive areas of the molecule are revealed by Fukui function, molecular electrostatic potential (MEP) and Hirshfeld surface studies. The human enzyme steroidogenic types and their protein targets were tested with this molecule by molecular docking.